2021
DOI: 10.4309/jgi.2021.48.11
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Measurement Invariance of the Financially Focused Self-Concept Construct

Abstract: Persons maintaining a financially focused self-concept view financial success as a core aspect of their respective self-concepts. We examined whether measurement properties of the financially focused self-concept scale (FFS) are invariant over time. A sample of predominantly older community members who gamble (N = 147) completed the 4-item FFS and Problem Gambling Severity Index (PGSI) twice, approximately four weeks apart. FFS had strong temporal measurement invariance and moderate-to-high temporal stability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The short 4-item version was administered in wave 2 and assessed responses to key statements, including "How I feel about myself is largely based on the amount of money I have," "My moods are influenced by the amount of money I have," "People will think less of me if I don't have a lot of money," and "The opportunities that are available to me depend on the amount of money I have." The factor structure of the 4-item version was recently replicated using confirmatory factor analysis and was shown to have strict temporal measurement invariance among community gamblers over a one-month period (Tabri et al, 2021a(Tabri et al, , 2021b. Response options for each item were anchored at "not at all" (1) and "extremely" (5).…”
Section: Financial Motivationmentioning
confidence: 99%
“…The short 4-item version was administered in wave 2 and assessed responses to key statements, including "How I feel about myself is largely based on the amount of money I have," "My moods are influenced by the amount of money I have," "People will think less of me if I don't have a lot of money," and "The opportunities that are available to me depend on the amount of money I have." The factor structure of the 4-item version was recently replicated using confirmatory factor analysis and was shown to have strict temporal measurement invariance among community gamblers over a one-month period (Tabri et al, 2021a(Tabri et al, , 2021b. Response options for each item were anchored at "not at all" (1) and "extremely" (5).…”
Section: Financial Motivationmentioning
confidence: 99%
“…The numerous and readily available gambling opportunities mean that avoiding gambling is difficult for people with gambling problems ( LaBrie et al., 2007 ; St-Pierre, Walker, Derevensky, & Gupta, 2014 ; Thomas et al., 2009 ), and as gambling has migrated to the internet, it has become readily accessible via mobile devices ( Abbott, 2020 ; Blaszczynski, Ladouceur, & Shaffer, 2004 ). Consequently, many people who problem gamble suffer from related economic, social, and health burdens ( Browne et al., 2016 ; Calado & Griffiths, 2016 ; Tabri, Philander, Wood, & Wohl, 2021 ; Wardle et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These four items have been shown to load on a single factor in cross-sectional research . As well, unpublished longitudinal research has shown that these four items have at least partial temporal measurement invariance (Tabri, 2023). My current research study extended existing research on the 4-item BAAS by examining its psychometric properties in the context of experience sampling.…”
Section: The Present Researchmentioning
confidence: 66%
“…Research has also shown that the average of the four items was internally consistent and positively correlated with measures of disordered eating in community samples (Tabri, Yung, & Elliott, 2022;. Furthermore, in unpublished psychometric longitudinal research, the 4-item BAAS has been shown to have temporal measurement invariance over a 4-month period among university women (Tabri, 2023). That is, the 4-item BAAS carries the same meaning over time.…”
Section: The Measurement Of Appearance Focused Self-conceptmentioning
confidence: 94%